Consequences of the hospital nursing research culture: Perspective of staff nurses - Ejercito Mangawa Balay-odao; Jonas Preposi Cruz; Joseph U. Almazan (Elsevier, 2024)
Objective: Research plays a critical role in molding nursing as a profession. Healthcare organizations are challenged to build an organizational culture that cultivates the development of nursing research. Creating a culture of nursing research is constantly branded a vital component in advancing nursing science. Therefore, this study described nurses' perceptions about their hospital's nursing research culture. Methods: Semi-structured personal interviews were used to collect data. Seventeen staff nurses were selected to participate in the study by purposive sampling method from December 2022 to April 2023 in the eastern Philippines. The researchers used Braun and Clarke's thematic approach to analyze the qualitative data. Results: The analysis revealed three central themes and seven subthemes: influencing behavior and performance of the employee (help in research information and learning, flexibility and adaptability, collaboration and communication among employees), influencing staff nurses' research participation (leadership strategies, training and professional development), and affecting hospitals to adapt to change (organizational performance and success, employee engagement and job satisfaction). Conclusions: The findings support the benefits of a positive nursing research culture in hospitals due to its critical role in shaping nurses' behavior and performance, participation in nursing research, and hospital adaptation to changes. Collectively, these themes contribute to a deeper understanding of the multifaceted impact that a culture of nursing research can have on various levels of the healthcare system.